Synthesis and Characterization of Nickel(II) and Copper(II) Complexes of The Schiff Bases Derived from 2,4,6-/3,5,6- Trimethyl-3-cyclohexene-1-carboxaldehyde and Glycine - GULER, ERSIN (Asian Journal of Chemistry, 2010)
In this study, the synthesis of Schiff bases derived from 2,4,6-trimethyl-3-cyclohexene-1-carboxaldehyde or 3,5,6- trimethyl-3-cyclohexene-1-carboxaldehyde and glycine and their complexes with nickel(II) and copper(II) were investigated. The synthesized compounds were characterized by elemental analyses, conductivity measurements, magnetic properties and FT-IR spectroscopy. The Schiff base ligands and their complexes have been further characterized by 1H NMR. The results showed that the Schiff base acts as a bidentate ligand which bonds to the metal ions through the imino nitrogen and carboxylate oxygen. The potassium salts of the Schiff bases are 1:1 electrolytes, but all the complexes are non-electrolytes.